HIV-1-Neutralizing IgA Detected in Genital Secretions of Highly HIV- 1-Exposed Seronegative Women on Oral Preexposure Prophylaxis - Lund, Jennifer M.; Broliden, Kristina; Pyra, Maria N.; Thomas, Katherine K.; Donnell, Deborah; Irungu, Elizabeth; Muwonge, Timothy R.; Mugo, Nelly; Manohar, Madhuri; Jansson, Marianne; Mackelprang, Romel; Marzinke, Mark A.; et al. (Journal of virology, 2016)
Although nonhuman primate studies have shown that simian immunodeficiency virus/simian-human immunodeficiency virus (SIV/SHIV) exposure during preexposure prophylaxis (PrEP) with oral tenofovir can induce SIV immunity without productive infection, this has not been documented in humans. We evaluated cervicovaginal IgA in Partners PrEP Study participants using a subtype C primary isolate and found that women on PrEP had IgA with higher average human immunodeficiency virus type 1 (HIV-1)-neutralizing magnitude than women on placebo (33% versus 7%; P 0.008). Using a cutoff of>90% HIV-1 neutralization, 19% of women on-PrEP had HIV-1-neutralizing IgA compared to 0% of women on placebo (P 0.09). We also estimated HIV-1 exposure and found that the proportion of women with HIV-1-neutralizing IgA was associated with the level of HIV-1 exposure (P 0.04). Taken together, our data suggest that PrEP and high levels of exposure to HIV may each enhance mucosal HIV-1-specific humoral immune responses in sexually exposed but HIV-1-uninfected individuals.
Keywords: HIV-1-Neutralizing IgA; Genital Secretions; Seronegative Women; Oral Preexposure Prophylaxis